Influence of Reading Material Characteristics on Study Time for Pre-Class Quizzes in a Flipped Classroom - Persky, Adam M. (Am J Pharm Educ, 2017)
Objective. To examine how instructor-developed reading material relates to pre-class time spent preparing for the readiness assurance process (RAP) in a team-based learning (TBL) course. Methods. Students within pharmacokinetics and physiology were asked to self-report the amount of time spent studying for the RAP. Correlation analysis and multilevel linear regression techniques were used to identify factors within the pre-class reading material that contribute to self-reported study time. Results. On average students spent 3.2 hours preparing for a section of material in the TBL format. The ratio of predicted reading time, based on reading speed and word count, and self-reported study time was greater than 1:3. Self-reported study time was positively correlated with word count, number of tables and figures, and overall page length. For predictors of self-reported study time, topic difficulty and number of figures were negative predictors whereas word count and number of self-assessments were positive predictors. Conclusion. Factors related to reading material are moderate predictors of self-reported student study time for an accountability assessment. A more significant finding is student self-reported study time is much greater than the time predicted by simple word count.